TINJAUAN ANALISIS HIDROLOGI BENDUNG (STUDI KASUS BENDUNG JANGKOK KECAMATAN NARMADA KABUPATEN LOMBOK BARAT) - Arswendra Arswendra; Bagus Widhi Dharma S.; I Gusti Ngurah Octova Seventilofa (LPPM PSDKU Kampus Mataram UNMAS Denpasar, 2021)
Weir is one of the government's efforts to provide irrigation water and increase agricultural production. Any construction of a weir requires an appropriate hydrological analysis so that the weir planning can be technically and economically appropriate. The objectives of this study are: to determine the planned discharge in the Jangkok watershed. In this study, a descriptive quantitative approach is used, meaning that the problems discussed in this study aim to explain the state of the phenomenon status, namely knowing things related to the state of something in accordance with the phenomenon or symptoms that occur. Based on the description above, several problems can be formulated, including: The calculation of the flood discharge plan used the Haspers and Der Weduwen methods, after calculating the two methods obtained a small deviation, namely the Haspers method = 0.071 to 0.086 while the peak time (Tp) = 7,718 hours, the peak discharge of the Snyder synthetic unit hydrograph equation was developed.